Increasing employee engagement through self-efficacy in Gen Z employees at coffee shops in Pontianak City - Sutilara, Erodea Exsi; Ginting, Sunardi (Institute of Computer Science (IOCS), 2025)
This study aims to analyse the role of self-efficacy as a moderator variable in the influence of role conflict on employee engagement of Generation Z employees working in coffee shops in Pontianak City. This study aims to examine how self-efficacy functions as a moderator variable in the relationship between role conflict and employee engagement among Generation Z workers in coffee shops in Pontianak City. The background of this study is based on the phenomenon of the younger generation's increasing involvement in the workforce, especially in the coffee shop industry, which demands high flexibility and adaptability. This study employs a quantitative approach, involving a total of 201 respondents. The sampling technique employed the snowball sampling method, and data analysis was facilitated by WarpPLS software version 7.0. The study's results indicate that role conflict has a positive and significant impact on employee engagement. In addition, self-efficacy has been proven to strengthen the relationship between role conflict and employee engagement, such that individuals with higher levels of self-efficacy are still able to exhibit more optimal commitment, motivation, and involvement despite facing role conflict in the workplace. Theoretically, this study contributes to the understanding of self-efficacy as a moderating factor that enhances engagement under conditions of role conflict. Practically, the findings provide insights for coffee shop managers to design interventions that enhance Gen Z employees’ self-efficacy, thus improving engagement even in high-stress environments.